2012
DOI: 10.1007/bf03261973
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Economic Burden of Adverse Drug Reactions among Elderly Patients in Ontario Emergency Departments

Abstract: Background: The rapid rise in the availability and use of pharmaceutical agents, and particularly polypharmacy, directly increases the risk for patients to experience adverse drug reactions (ADRs). There are few studies on the overall incidence and costs of ADRs.Objective: The aim of this study was to estimate the incidence and costs of emergency department (ED) visits related to ADRs for patients greater than 65 years of age using administrative data, and to describe risk factors for experiencing severe ADRs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
96
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 30 publications
5
96
2
1
Order By: Relevance
“…Female gender is considered important risk factors for ADRs. 3,4 Other Indian spontaneous reporting studies had also observed high percentage of ADRs in female. 15,16,20 However, Jose and Rao observed similar incidence of 0.15% for both genders.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Female gender is considered important risk factors for ADRs. 3,4 Other Indian spontaneous reporting studies had also observed high percentage of ADRs in female. 15,16,20 However, Jose and Rao observed similar incidence of 0.15% for both genders.…”
mentioning
confidence: 92%
“…1,2 The female gender, elderly age group, multiple medications and the recent introduction of new drugs are important risk factors for ADRs. 3 Other important factors for their occurrence are race, pregnancy, breastfeeding, alcohol intake, and state of liver and kidney functions. 4 Antimicrobial drugs and analgesics are most frequently responsible for ADRs.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,11 The Y40-Y59 external cause codes captured about 80% of hospitalisations with "drug-induced" or "due to drug" diagnosis codes, a much higher concordance than the 12-15% reported using English hospital statistics more than a decade ago. 11 Adding high-probability ADR-related diagnosis codes to external cause-based selection yielded a 10.4% increase in ADR numbers on a frequency basis, such that 2.2% of hospitalisations, in this Australian context, were classified as an ADR-related event; this is consistent with a 2-3% national figure based on a recent review.…”
Section: Discussionmentioning
confidence: 93%
“…5 ADR surveillance may use International Classification of Diseases (ICD) codes (9th or 10th revisions) to ascertain ADRs from routinely collected data on deaths, hospitalisations and emergency department visits. [6][7][8][9][10][11][12][13] These ICD codes comprise diagnoses describing specific clinical symptoms and signs indicating any ADRs (e.g. D61.1 -drug-induced aplastic anaemia), and supplementary classifications documenting external causes to ADR indications (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation